PEMBAHARUAN BUKU AJAR EVOLUSI BERBASIS PENELITIAN UNTUK MAHASISWA S1 PENDIDIKAN BIOLOGI UNIVERSITAS SIMALUNGUN - IKA ROSENTA PURBA (LP2MTBM MAKARIOZ, 2020)
The aim of this research is to develop the evolution textbook based on research for Simalungun University. Result of development research is a textbook draft which it is validated. Validation process conducted by matter experts, instructional media experts, practitioner, and individual testing by nine students. Validation results of matter expert is 92%, in very valid categories. Validation result of instructional media experts was 92%, in very valid categories. Validation results practitions was 74% in valid enough categories. Individual testing results by students was 81% in valid enough categories. Revision based on validation results in quantitaty and qualitative data.